Synthesis of Poly(methyl methacrylate)-b-poly(N-isopropylacrylamide) Block Copolymer by Redox Polymerization and Atom Transfer Radical Polymerization - Melahat Göktaş; Guodong Deng (Universitas Gadjah Mada, 2018)
Poly(methyl methacrylate)-b-poly(N-isopropylacrylamide) [PMMA-b-PNIPAM] block copolymers were obtained by a combination of redox polymerization and atom transfer radical polymerization (ATRP) methods in two steps. For this purpose, PMMA macroinitator (ATRP-macroinitiator) was synthesized by redox polymerization of methyl methacrylate and 3-bromo-1-propanol using Ce(NH4)2(NO3)6 as a catalyst. The synthesis of PMMA-b-PNIPAM block copolymers was carried out by means of ATRP of ATRP-macroinitiator and NIPAM at 60 °C. The block copolymers were obtained in high yield and high molecular weight. The characterization of products was accomplished by using multi instruments and methods such as nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy, gel permeation chromatography, and thermogravimetric analysis.